Factors associated with in-hospital outcomes in 594 consecutive patients suffering from severe blunt chest trauma. (June 2015) - Söderlund, T.; Ikonen, A.; Pyhältö, T.; Handolin, L.
Background and Aims: Blunt thoracic injury is a common cause for hospital admission after trauma. The effect of the number of rib fractures on the outcome is controversial. In this study, our hypothesis was that an increasing number of rib fractures correlates with mortality and hospital resource utilization. In addition to mortality, our focus was on the length of stay at hospital and in the intensive care unit, ventilator days, and the days in continuous positive airway pressure. Material and Methods: The present investigation is a retrospective study from a single trauma center. The study includes patients with severe thoracic injury (thoracic Abbreviated Injury Scale (AIS) > 2) admitted to hospital after blunt trauma. Patients with isolated thoracic spine injuries and patients who were dead on arrival were excluded. Vital signs, laboratory results on admission, given care, intensive care unit and hospital length of stay, injuries, and in-hospital mortality were collected for the study. Results: A total of 594 patients from a 5-year period (2003–2007) were included in the study. The mean age of the patients was 45 years, and 76.9% of the patients were males. The average Injury Severity Score was 22, and the patients had on average 5.5 injuries. Overall mortality was 6.4%. In the multivariate analysis, the mortality was associated with base excess and tromboplastin time in admission. The number of rib fractures did not correlate with the outcome measures, but the presence of bilateral rib fractures correlated with the outcome measures other than mortality. Conclusions: The number of rib fractures does not correlate with mortality or the length of stay in the intensive care unit in blunt trauma patients with severe thoracic injury. Mortality in these patients correlated with the degree of hypoperfusion (base excess) and coagulation abnormalities (tromboplastin time) on admission.